Theoretical and methodological strategies for the development of marketing activities management - Maximyuk, Y.; Gavrikov, D.; Borodavko, M. (Ways to Improve Construction Efficiency, 2018)
The theoretical approaches to the assessment of competition in the markets are reviewed. research and improvement of the classification of factors of influence on the choice of marketing strategy of the enterprise. The distribution and systematization of the factors of the internal and external environment by classification groups is carried out. The expediency and necessity of taking into account certain factors during the formation and selection of marketing strategy of enterprise development is substantiated. Market research environment that can directly influence the success or failure of an organization, which allows analysis of various market factors and the ability of management to refine its strategy and strengthen the position of the company in relation to competitors.